Music listening and performance: the artistic and psychopedagogical relationship - ROSOGA-POPA, Daniela Carmen (Acta et Commentationes, Sciences of Education, 2026)
The paper examines the relationship between music listening and performance from both artistic and psycho-pedagogical perspectives, highlighting their complementarity in musical education. Listening is defined as an active process of understanding and emotional engagement, in which the listener becomes a conscious participant, capable of perceiving musical structures and meanings. Performance is presented as a creative and expressive act that combines knowledge with emotional experience and artistic communication. The relationship between the two is bidirectional: listening enhances understanding, while performance consolidates musical experience. Their integration contributes to the development of musical thinking, artistic sensitivity, and aesthetic taste.